Penggunaan Bahasa Indonesia Baku di Kalangan Mahasiswa Pada Base Twitter Colle - Aprilianti, Amelia; Fadillah, Firda; Salma, Azhar (Jurnal Bahasa dan Sastra, 2024)
Twitter as the main platform for online interaction plays an important role in digital communication, including the definition of language, its role in online communication, as well as the influence and impact of using Indonesian on Twitter. In communication, the use of language is very influential in conveying the content of what is being discussed. Language is also recognized as a national identity that we must love and be proud of as the nation's successors. This research uses qualitative methods and data collection strategies through content analysis and research analysis through questionnaires. Understanding the use of standard and non-standard language is also a key aspect in this analysis. From here we know the results that the use of Indonesian on the Twitter base gets a balanced response between those who use Indonesian and those who don't, with a gain of 43.8%, then use good and correct Indonesian when sending a message or replying to a message on the base. colle with results: Yes: 43.8%, No: 43.8%, next is the use of non-standard Indonesian more than those who already use standard Indonesian.